O Serviço Social nas operadoras de planos privados de assistência à saúde: demandas, atribuições e respostas profissionais - Soares, Joseneide Costa (2008)
The present study deals with the exercise of professional social workers in private health care plans registered with the Regional Council of Medicine/RN, in the city of Natal/RN, with regards to the demands/tasks, work conditions, and the professional response, given the climate of restructuring the capital. The set of socio-historical transformations, as a results of the dynamic capitalist, is a process of new configurations in relation to state and society that interfere directly in relation to working conditions, social rights historically won by workers. In this context, the operator of health plans arises as a possibilities to provide services in health, through the logic of the market, in which the subjects of law, become consumers contributing to the displacement of the responsibilities of the State. Obligating workers to lessen the burden with the reproduction of their workforce. This involves changing societal context for social service, since it is one of the professions that are active in terms of the immediate social issue, and come as part of the collective worker. From qualitative research based on a theoretical and methodological perspective and critical dialectics, it was possible to unveil some features and trends of the exercise of(a) social operators in private health care plans. The survey results indicated that : a) the demands and duties for certain social service, are associated with the redevelopment of the capital, whose requirements and responsibilities professionals have with their needs, particularly the guarantee of profit, services rendered; b) in the conditions of work there is a trend of insecurity uncertainty and dismantling of professionals; c) the answers professionals suffer the limits and contradictions present in the daily training, mainly depending one the characteristics of management and operation of the operators, which has professional relative autonomy